Oxygen induced strong mobility modulation in few-layer black phosphorus. (1st February 2017) - Han, Cheng; Hu, Zehua; Carvalho, Alexandra; Guo, Na; Zhang, Jialin; Hu, Fang; Xiang, Du; Wu, Jing; Lei, Bo; Wang, Li; Zhang, Chun; H Castro Neto, A; et al.
Abstract: 2D black phosphorus configured field-effect transistors generally show a hole-transport-dominated ambipolar characteristic, owing to the severely restricted electron mobility by air ambient. Here, we demonstrate the strongly modulated mobility of few-layer black phosphorus in contact with oxygen. Pure oxygen exposure can dramatically decrease the electron mobility of black phosphorus by over three orders of magnitudes without degrading the hole transport. In situ x-ray photoelectron spectroscopy characterization reveals the physisorption nature of oxygen on black phosphorus. Density functional theory calculations identify the unoccupied states of molecular oxygen physisorbed on few-layer black phosphorus, that serves as electron trap but not as hole trap, consistent with the aforementioned mobility modulation. In contrast, oxygen exposure upon light illumination exhibits a significant attenuation for both electron and hole transport, originating from the photoactivated oxidation of black phosphorus, as corroborated by in situ x-ray photoelectron spectroscopy measurements. Our findings clarify the predominant role of oxygen in modulating transport properties of black phosphorus, thereby providing deeper insight to the design of black phosphorus based complementary electronics.